Nasikh Mansukh's Implications for the Implementation of the Director General of Islamic Community Guidance Decree No. 379 of 2018 concerning Marriage Guidance to Prevent Divorce (Study at KUA Panca Rijang District, Sidrap Regency) - Akram Akkas; Hannani; Zainal Said; Agus Muchsin; M. Ali Rusdi (Universitas Muhammadiyah Palu, 2024)
Regulation of the Director General of Islamic Community Guidance at the Ministry of Religion Number 379 of 2018 instructs that every man and woman who wishes to get married must follow marriage guidance organized by the Ministry of Religion and accredited Islamic religious organizations. Certain laws will be replaced by new laws in the future, which will then be known as Nasakh Mansukh. This thesis discusses the implications of Nasikh Mansukh for the implementation of the Decree of the Director General of Islamic Community Guidance Number 379 of 2018 concerning Marriage Guidance to Prevent Divorce. The results of this research show that the implementation of marriage guidance (Bimwin) in Panca Rijang District, Sidrap Regency for prospective brides and grooms in creating a sakinah family. Nasikh Mansukh's implications for the implementation of Islamic Guidance Regulation No. 379/2018 regarding marriage guidance does not have Nasikh Mansukh, but rather complements and strengthens the previous regulations and can be said to be bayan taqrir.